Use of anti-seizure medications in different types of autoimmune encephalitis: A narrative review - Du, Jinyuan; Guo, Yi; Zhu, Qiong (Frontiers in Neurology, 2023)
Seizures are the main manifestation of the acute phase of autoimmune encephalitis (AE). Anti-seizure medications (ASMs) play an important role in controlling seizures in AE patients, but there is currently a lack of consensus regarding the selection, application, and discontinuation of ASMs. This narrative review focuses on the use of ASMs in patients with AE driven by different antibodies. The PubMed, Embase, and MEDLINE databases were searched up until 30 October 2022 using prespecified search terms. We identified 2580 studies; 23 retrospective studies, 2 prospective studies and 9 case reports were evaluated based on our inclusion criteria. Anti-N-methyl-D-aspartic-acid-receptor (anti-NMDAR) encephalitis is the type of AE that responds best to ASMs, and long-term or combined use of ASMs may be not required in most patients with seizures; these results apply to both adults and children. Sodium channel blockers may be the best option for seizures in anti-leucine-rich-glioma-inactivated-1 (anti-LGI1) encephalitis, but patients with anti-LGI1 encephalitis are prone to side effects when using ASMs. Cell surface antibody-mediated AE patients are more likely to use ASMs for a long period than patients with intracellular antibody-mediated AE. Clinicians can score AE patients’ clinical characteristics on a scale to identify those who may require long- or short-term use of ASMs in the early stage. This review provides some recommendations for the rational use of ASMs in encephalitis mediated by different antibodies with the aim of controlling seizures and avoiding overtreatment.